Assessing commitment to reflection: Perceptions of medical students - Poirier, Joanie; Ouellet, Kathleen; Désilets, Valérie; Graillon, Ann; Xhignesse, Marianne; St-Onge, Christina (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Background: While developing reflection skills is considered important by educators, the assessment of these skills is often associated with unintended negative consequences. In the context of a mandatory longitudinal course that aims to promote the development of reflection on professional identity, we assessed students’ commitment to reflection. This study explores students’ perception of this assessment by their mentor.Methods: We conducted a qualitative descriptive study using semi-structured interviews with twenty-one 1st and six 2nd year medical students. Thematic analysis was informed by Braun and Clarke’s six-step approach.Results: We identified four main themes: 1- assessment as a motivator, 2- consequences on authenticity, 3- perception of inherent subjectivity, and 4 - relationship with the mentor.Conclusions: In the context of assessing reflection skills in future physicians, we observed that students –when assessed on the process of reflection– experienced high motivation but were ambivalent on the question of authenticity. The subjectivity of the assessment as well as the relationship with their mentor also raises questions. Nevertheless, this assessment approach for reflective skills appears to be promising in terms of limiting the negative consequences of assessment.